THE EFFECTS OF DIGITAL COMIC ON STUDENT’S READING COMPREHENSION OF VOCATIONAL SCHOOL STUDENTS (RETAIN, 2023)
This study aims to investigate the effect of using digital comics on students' reading comprehension in vocational school. The study was conducted in two vocational high school research classes. This study uses a Quasi Experimental Study design, rooted in the principles of experimental research, to examine the impact of student's reading ability on their learning activities. The results show that digital comic was effective in increasing one of the reading aspect namely, identify word meaning, it had significance differences by the mean score of before and after the treatment with t-test result has a greater value by Sig. It is suggested that more frequent implementation of digital comic activities, along with repetition in classroom instruction, can yield positive results and improve various aspects of reading comprehension. The researcher suggests that future research on digital comic should be conducted with a deeper exploration of different genres.